2008
DOI: 10.1016/j.jns.2007.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem neuropathology in a mouse model of Niemann–Pick disease type C

Abstract: Niemann-Pick disease type C (NPC) is a neurovisceral lipid storage disorder characterized by progressive and widespread neurodegeneration. Although some characteristic symptoms of NPC result from brainstem dysfunction, little information is available about which brainstem structures are affected. In this study, the brainstems of mutant BALB/c NPC1-/- mice with a retroposon insertion in the NPC1 gene were examined for neuropathological changes. In the midbrain, the integrated optic density (IOD) and cell count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…In human NPC disease, imaging studies have found that the thalamus amongst other structures has an altered signal compared to controls (Huang et al, 2011; Walterfang et al, 2010). Interestingly, there is evidence for selective pathology at multiple steps of sensory pathways in Npc1 −/− mice, with degeneration at the level of the sensory dorsal root ganglion (Ohara et al, 2004) and brain stem nuclei (Luan et al, 2008). Our data shows that the somatosensory thalamocortical pathway (VPM/VPL connecting to S1BF) displayed the most pronounced pathology, with the interconnected Po nucleus that also relays somatosensory input similarly displaying localised reactive gliosis (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In human NPC disease, imaging studies have found that the thalamus amongst other structures has an altered signal compared to controls (Huang et al, 2011; Walterfang et al, 2010). Interestingly, there is evidence for selective pathology at multiple steps of sensory pathways in Npc1 −/− mice, with degeneration at the level of the sensory dorsal root ganglion (Ohara et al, 2004) and brain stem nuclei (Luan et al, 2008). Our data shows that the somatosensory thalamocortical pathway (VPM/VPL connecting to S1BF) displayed the most pronounced pathology, with the interconnected Po nucleus that also relays somatosensory input similarly displaying localised reactive gliosis (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…With the use of the tetO-Npc1-YFP transgenic mouse strain generated for this study, future studies can take advantage of gene delivery of a tTA transgene, or other existing mouse driver lines, to target the thalamus or other CNS areas affected in Npc1 −/− mice, such as the brainstem (Luan et al, 2008). The targeting of increasingly discrete neuronal networks and the development of assays to measure specific behaviors will be useful in order to associate rescue of a particular neural circuit with improvements to health-related quality of life, prolonged lifespan, and inhibition of neurological signs.…”
Section: Discussionmentioning
confidence: 99%
“…The most striking consequence of NPC1 deficiency in the brains of mice and humans is a profound loss of Purkinje neurons in the cerebellum (103)(104)(105). In other regions of the brain, such as the cerebral cortex and thalamus, neuronal apoptosis also occurs but is less common than axonal swelling and ectopic dendrite formation ( 51,52,(106)(107)(108)(109). The reason why Purkinje neurons are the most sensitive neurons to NPC defi ciency is not clear ( 39 ).…”
Section: Loss Of Npc Function In Cells Of the Brainmentioning
confidence: 99%